Does stakeholder pressure matter in Islamic banks’ corporate social responsibility and financial performance? - Muhammad, Ali; Sadia, Mehfooz Khan; Chin Hong, Puah; Muhammad Shujaat, Mubarik; Muhammad, Ashfaq (Emerald Publishing Limited, 2022)
Abstract Purpose – This study aims to examine the impact of stakeholder pressure on Islamic banks’ corporate social responsibility (CSR) practices and financial performance. Design/methodology/approach – A close-ended questionnaire was collected from 282 Islamic bank’s branch managers. Partial least square structural equation modeling was used to test the hypothesized model. Both measurement and structural models were found to be fit for this research. Findings – Results indicate that all components of stakeholder pressure (management, client, competitor, Sharia advisory board and community) have a significant positive impact on Islamic CSR. The findings of this study further revealed that Islamic CSR is a significant predictor of bank’s financial performance. Based on the present empirical results, this study suggests that Islamic bank managers should develop the best CSR practices to gain a competitive advantage and sustainable financial performance. Originality/value – Overall, this study contributes significantly to the Islamic bank CSR literature. However, to the best of the authors’ knowledge, few studies have been conducted to establish a link between firm performance and CSR in Islamic banks using a comprehensive model of stakeholder pressure.